Isolated impact of liver herniation on outcome in fetuses with congenital diaphragmatic hernia: a matched-pair analysis based on fetal MRI relative lung volume - Weis, Meike; Hoffmann, Stephanie; Henzler, Claudia; Weiß, Christel; Schönberg, Stefan; Schaffelder, Regine; Schaible, Thomas; Neff, Wolfgang (European journal of radiology, 2018)
PURPOSE: To evaluate liver-herniation as individual parameter on outcome in children with congenital diaphragmatic hernia. - MATERIALS AND METHODS: In a retrospective matched-pair analysis based on observed to expected fetal lung volume (o/e FLV), birth weight, gestational age at time-point of examination, status of tracheal occlusion therapy and side of the defect the individual impact of liver-herniation on survival, need for extracorporeal membrane oxygenation (ECMO) therapy and chronic lung disease (CLD) was investigated. In total 61 pairs (122 patients) were included. Fisher's exact test was used to evaluate influence of liver-herniation and a p-value of <0.05 was defined as statistically significant. The study was approved by the local review board. - RESULTS: Children with liver-herniation have lower survival rates (78.7% vs. 95.1%; p=0.0073), need ECMO-therapy more often (41.0% vs. 16.4%; p=0.0027) and are more likely to develop CLD (71.7% vs. 37.9%; p=0.0004) than their corresponding matched-pair without liver-herniation. - CONCLUSION: Liver-herniation itself and not further lung-volume restriction due to liver-herniation is responsible for poor outcome in CDH.
Gesehen am 04.07.2019